Accessibility of Information Communication Technology and Its Motivation on Learning in Secondary Schools and Colleges - Erastus, Kato Masika (New Visions in Science and Technology Vol. 6, 2021)
The objective of this study was to establish the extent to which Information and Communication Technology (ICT) use and its accessibility motivation had enhanced student centred learning (SCL) skills among public secondary school students in Bungoma County, Kenya. The government of Kenya together with non-governmental agencies partnered to develop capacity in terms ICT infrastructure and manpower across the country. The study hypothesis was derived from the study objective. The target population was 742 respondents in 71 schools and sample size was 272 respondents selected from 19 schools. This study adopted mixed methods design. The tools used for data collection were questionnaires and an interview guides. Cronbach’s alpha for reliability test was 0.713. Descriptive statistics such as frequencies, percentages and means were employed while inferential statistics were correlation and regression analyses. Data was analyzed with the help of the Statistical Package for Social Sciences (SPSS). Qualitative data was analyzed through content analysis. The simple linear stepwise multiple regression results indicated that ICT accessibility and its motivation had a significant impact on SCL. The study’s recommendations were: school managers to improve on ICT accessibility motivation by enhancing anytime anywhere accessibility through use of portable technologies. The findings of this study may be used to guide the school managers on the need to improve ICT accessibility requirements necessary for the enhancement of SCL.